Multicultural Counseling Awareness School Counselor in Area 3 T (Lebak Banten) - Iis Solihah (Proceeding International Conference on Religion, Science and Education, 2023)
Indonesia is a country rich in cultural diversity (multicultural). Cultural diversity is a natural event due to the meeting of various cultures, interacting with various kinds of individuals from different backgrounds and having different ways of life. The diversity of counselees such as different cultural backgrounds, religions, ethnicities, races interact with each other in the school community and this requires understanding and cultural awareness which is not easy. As a counselor who is responsive to multicultural issues, it seems necessary to develop awareness, knowledge and skills to intervene effectively in providing counseling services to students from diverse cultural backgrounds. This research method is a descriptive-quantitative survey. The research subjects were 30 counselors in the Lebak-Banten area. Data collection used a multicultural awareness scale while data analysis used SmartPLS 3. The results showed (1) there was a positive and significant influence between the teacher’s interaction with students in the counseling process (p=0.000). (2) There is a positive and significant relationship between language knowledge & cultural background between teachers and students (p=0.000).